2018
DOI: 10.3389/fmicb.2018.00375
|View full text |Cite
|
Sign up to set email alerts
|

Factors Involved in the Persistence of a Shiga Toxin-Producing Escherichia coli O157:H7 Strain in Bovine Feces and Gastro-Intestinal Content

Abstract: Healthy cattle are the primary reservoir for O157:H7 Shiga toxin-producing E. coli responsible for human food-borne infections. Because farm environment acts as a source of cattle contamination, it is important to better understand the factors controlling the persistence of E. coli O157:H7 outside the bovine gut. The E. coli O157:H7 strain MC2, identified as a persistent strain in French farms, possessed the characteristics required to cause human infections and genetic markers associated with clinical O157:H7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 85 publications
1
29
0
Order By: Relevance
“…Because of the loss of viability of the E. coli commensal population after thawing of the BSIC samples (see the ‘Experimental procedures’ section), aspartate utilization was also analysed in a bovine commensal E. coli strain. The strain BG1, used as reference bovine commensal E. coli in previous studies (Bertin et al, , ; Segura et al, ) has been isolated from the small intestine of a cow at slaughter (Bertin et al, ). The whole genome of BG1 has been recently sequenced (Genbank accession number MOAH00000000) and analysed (Segura et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the loss of viability of the E. coli commensal population after thawing of the BSIC samples (see the ‘Experimental procedures’ section), aspartate utilization was also analysed in a bovine commensal E. coli strain. The strain BG1, used as reference bovine commensal E. coli in previous studies (Bertin et al, , ; Segura et al, ) has been isolated from the small intestine of a cow at slaughter (Bertin et al, ). The whole genome of BG1 has been recently sequenced (Genbank accession number MOAH00000000) and analysed (Segura et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, oxygen tension may fluctuate in the mammal intestine due to dynamic cycles of oxygen diffusion and oxygen consumption by facultative anaerobes and E. coli must rapidly respond to oxygen availability to survive in the mammal gut (Cole, 1996;Jones et al, 2007Jones et al, , 2011. In the absence of a suitable in vivo model, we designed in vitro growth conditions, corresponding to partial anaerobiosis, previously used in our laboratory to mimic the environment of the bovine small intestine (Bertin et al, 2011(Bertin et al, , 2013(Bertin et al, , 2014Segura et al, 2018). The bacterial suspensions were constituted by a mixture of bacteria, a part of them having access to oxygen while another part being under anaerobiosis, reflecting thereby the aeration conditions encountered in the mammalian small intestine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Segura et al . ) and different diarrheagenic strains of E. coli might have different subsets of genes involved in binding or multiple mechanisms for binding to plant surfaces (Jeter and Matthysse ). We concluded that, for baby leaf spinach, rocket and Swiss chard, plant species, but not cultivar, affects colonization by E. coli O157:H7 gfp+ .…”
Section: Discussionmentioning
confidence: 99%
“…However, our model strain was Shiga toxin negative, the results of the present study need to be verified for Shiga toxigenic E. coli outbreak strains. Shiga toxin genes might be indirectly involved in intestinal colonization (Baines et al 2008;Segura et al 2018) and different diarrheagenic strains of E. coli might have different subsets of genes involved in binding or multiple mechanisms for binding to plant surfaces (Jeter and Matthysse 2005). We concluded that, for baby leaf spinach, rocket and Swiss chard, plant species, but not cultivar, affects colonization by E. coli O157:H7 gfp+.…”
Section: Spinachmentioning
confidence: 95%